Pekalongan Aquatic Center (Penekanan Pada Stadion Kolam Renang Indoor) - Urrohman, M. Aalaa; , Ir. Alpha Febela Priyatmono, M.T (2017)
Pekalongan is the one of 35 districts in Central Java. It is located in west of north coast along north coasts of Java Sea which elongated to south with Kajen city as the capital and central government. The aquatic sport interest development especially swimming in Pekalongan is well. Even recreation concept swimming pool is a lucrative business. It is proved by 5 swimming pools, but none of them is national or international standard to swimming race, while swimming athletes require it to train and improve swimming expertise and achievement. The Pekalongan Aquatic Center (PAC) is a design planning which is expected to solve the problem. The PAC goal is as society sport vehicle to improve the health and life quality both in education and recreation sports. The Pekalongan Aquatic Center (PAC) target is as a medium to improve the aquatic athlete achievement in Pekalongan by international building standard and modern contemporary architecture concept. Keywords: Pekalongan, Aquatic Center, Architecture, Modern Contemporary